SISTEM NETWORK SHARING SOLUTION PADA BTS GSM/EDGE MENGGUNAKAN METODE MULTI-OPERATOR BSS (MOBSS) DI PT.INDOSAT.TBK MEDAN - Yussa Ananda (Jurnal Simetri Rekayasa, 2021)
This study discusses the implementation of a network sharing solution system with the Multi-Operator BSS (MOBSS) method which is applied to PT.INDOSAT.TBK Medan. Network sharing is a breakthrough in the telecommunications world that allows two or more operators to use a shared network or infrastructure. From the results of this study, it can be seen that the advantages of using this network sharing solution system are that operators can improve the efficiency of telecommunication networks both in terms of investment (CAPEX) and operations and maintenance (OPEX), as well as helping government programs in saving electricity. From the results of research on BTS KTRGUBERNURMDN (eg BTS sharing owned by Indosat) it is known that this BTS has two sectors, namely BTS ID 420 and BTS ID 421, where BTS ID 420 is BTS on service owned by Indosat while BTS ID 421 is BTS on service as another operator is “OPR A”. From the test results using a test call using Indosat operator signals, it is known that telephone calls use Channel Number H731, TRX 3 with timeslot position in slot 6. on slot 2.